Islamisasi Ilmu dalam Pendidikan: Telaah Buku Filsafat Pendidikan Islami Karya Ahmad Tafsir - Muhammad Farij Al-Kahfi; Mahmud Arif; Ridwan Faqih Sihono (Jurnal Budi Pekerti Agama Islam, 2025)
The development of modern scientific knowledge, which tends to be secular, has created a dichotomy between religious sciences and general sciences within Islamic education systems. This condition has encouraged the emergence of the idea of the Islamization of knowledge as an effort to restore knowledge to a tawhidic framework. This study aims to examine how the concept of the Islamization of knowledge is represented in Ahmad Tafsir’s book Filsafat Pendidikan Islami. This research employs a qualitative library study using content analysis and a philosophical approach to both the primary text and supporting literature. The findings show that although Ahmad Tafsir does not explicitly use the term “Islamization of knowledge,” the idea is strongly reflected in his construction of epistemology, his concept of the human person, the curriculum, and the educational processes he proposes. At the epistemological level, Tafsir positions revelation as the highest source of value that guides reason and experience, aligning with the principles of the Islamization of knowledge that reject secularist assumptions in the development of knowledge. In the domain of curriculum and educational design, the integration of religious sciences and modern sciences becomes a foundational principle that eliminates the dichotomy of knowledge and emphasizes a tawhidic orientation. The educational process is understood as a space for value internalization, character formation, and moral exemplarity, uniting knowledge with ethics. This study concludes that Ahmad Tafsir’s thought provides an important contribution to the development of an integrative Islamic educational paradigm rooted in tawhid while remaining responsive to the dynamics of modern scientific knowledge.